Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Theorem: Given two linear mappings $f,g: V \rightarrow V$ with

  • $f\circ g = g\circ f = 0$
  • $f+g=\operatorname{id}_V$
  • $f\circ f = f$
  • $g\circ g=g$

Then we have $$V=\operatorname{im}(\,f)\oplus \operatorname{im}(\,g)$$


I think $f$ and $g$ then are some kind of projections, where $f$ sets some coordinates to zero and $g$ sets exactly the remaining components two zero. It is clear to me, that the statement then is correct but how to show it formally?

share|cite|improve this question
Hint: In addition to $im(f), im(g)$, also think about $ker(f), ker(g)$. – vadim123 Dec 12 '13 at 18:14
up vote 3 down vote accepted
  1. Since $\operatorname{id}_V = f+g$, for any $v \in V$, $v = \operatorname{id}_V(v) = (f+g)(v) = f(v) + g(v)$. What does this imply about $\operatorname{im} f + \operatorname{im} g \subseteq V$?

  2. Let $v \in \operatorname{im} f \cap \operatorname{im} g$, so that $f(x) = v = g(y)$ for some $x$, $y \in V$. In light of your conditions on $f$ and $g$, what do you learn if you apply $f$ to both sides of the equation $f(x) = g(y)$? What do you learn if you apply $g$ instead?

share|cite|improve this answer
Then we have $im(g)+im(f)=V$, because of (2) we have $im(f)\cap im(g)= \lbrace 0_V \rbrace$, thus $im(g)\oplus im(f)=V$ ? – user127.0.0.1 Dec 12 '13 at 18:33
Oh, i see the exactly this in the other answer.. tyvm :) – user127.0.0.1 Dec 12 '13 at 18:35

Choose $ v\in V $. Since $ f+g=id_V $, we have $ f (v)+g (v)=v $. So $ V=im (f )+im (g) $. In order to prove that this is a direct sum, we need to prove that $ im (f)\cap im(g)=(0)$. Choose $y $ in the intersection. Then $ y=f (a)=g (b) $ for some $ a, b\in V $. Then $ f\circ f (a)= f\circ g (b) $. But $ f\circ g=0 $ and $ f\circ f=f $. So $ f (a) =0 $. Hence, $ y= 0 $. Therefore as required the intersection is (0) and $ V=im (f)\oplus im (g) $.

share|cite|improve this answer

Hint:$V=kerf\oplus imf$ because $f^2=f$. What is the relation of $kerf$ and $img$?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.